2013
DOI: 10.3390/ijms140918256
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of α-Tocotrienol on Kainic Acid-Induced Neurotoxicity in Organotypic Hippocampal Slice Cultures

Abstract: Vitamin E, such as alpha-tocopherol (ATPH) and alpha-tocotrienol (ATTN), is a chain-breaking antioxidant that prevents the chain propagation step during lipid peroxidation. In the present study, we investigated the effects of ATTN on KA-induced neuronal death using organotypic hippocampal slice culture (OHSC) and compared the neuroprotective effects of ATTN and ATPH. After 15 h KA (5 μM) treatment, delayed neuronal death was detected in the CA3 region and reactive oxygen species (ROS) formation and lipid perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Therapeutic effects of α-tocopherol by application of vitamin E in neurological lesions caused by neuronal excitotoxicity and the conditional activation of neuroglial cells have also been reported. In KA treatment-induced oxidative stress [ 166 ], delayed neuronal death was detected in the hippocampal CA3 region and ROS formation and lipid peroxidation were also increased. Both co-treatment and post-treatment with α-tocopherol (100 µM) or α-tocotrienol (100 µM) significantly increased cell survival and reduced the number of TUNEL-positive cells in the CA3 region.…”
Section: Role Of Antioxidants In the Brainmentioning
confidence: 99%
“…Therapeutic effects of α-tocopherol by application of vitamin E in neurological lesions caused by neuronal excitotoxicity and the conditional activation of neuroglial cells have also been reported. In KA treatment-induced oxidative stress [ 166 ], delayed neuronal death was detected in the hippocampal CA3 region and ROS formation and lipid peroxidation were also increased. Both co-treatment and post-treatment with α-tocopherol (100 µM) or α-tocotrienol (100 µM) significantly increased cell survival and reduced the number of TUNEL-positive cells in the CA3 region.…”
Section: Role Of Antioxidants In the Brainmentioning
confidence: 99%
“…Moreover, cell culture studies have demonstrated the neuroprotective effects of vitamin E, with tocotrienol being more potent than tocopherol [ 27 – 29 ]. The mechanisms of action of tocotrienol includes but not limited to free radical scavenging and modulation of arachidonic acid metabolism [ 28 , 30 32 ], kainic acid metabolism [ 33 ], homocysteic acid metabolism [ 34 ], and mitochondrial metabolism [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin C serves as aqueous phase antioxidant and its antioxidant potential is reported against carbofuran‐induced oxidative stress in rat brain and erythrocytes . Vitamin E, a group of tocopherols and tocotrienols existing in alpha, beta, gamma, and delta forms, is an important component of biological membrane having both antioxidant and nonantioxidant functions . α‐Tocopherol and α‐tocotrienol forms of vitamin E exhibit highest biological activity .…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E, a group of tocopherols and tocotrienols existing in alpha, beta, gamma, and delta forms, is an important component of biological membrane having both antioxidant and nonantioxidant functions . α‐Tocopherol and α‐tocotrienol forms of vitamin E exhibit highest biological activity . Vitamin E protects biomolecules by scavenging lipid peroxyl radicals and terminating the lipid peroxidation chain reaction .…”
Section: Introductionmentioning
confidence: 99%